Functions of identity in the context of being a student: Development and validation of the Functions of Student Identity Scale - Moreira, Paulo (2021)
A promising approach to the understanding of identity is the identity functions framework. However, its developmental specificities associated with adolescence remain unexplored. The aim of this study was to develop and test a new measure of the functions of identity as they relate to being a student. Consistent with the theoretical framework, an exploratory analysis with a subsample of high school students revealed five identity functions. A confirmatory analysis with a second subsample found that a higher-order model incorporating these five subscales demonstrated good fit to the data. A bifactor model and statistical indices indicated that it is appropriate to interpret a total student identity score using this instrument. The five subscales, and total scale, demonstrated good convergent validity with a measure of academic behavioral change. These preliminary results suggest that this new instrument presents good psychometric properties and that it is a suitable assessment instrument for the measurement of students’ processes and outcomes. For example, its associations with academic performance stages of changes suggest that this instrument will be useful for identifying students at risk for poor academic trajectories.